2001
DOI: 10.1097/00041327-200106000-00015
|View full text |Cite
|
Sign up to set email alerts
|

The SKILL Card Test in Optic Neuritis: Experience of the Optic Neuritis Treatment Trial

Abstract: The SKILL Card difference score is not a meaningful measure for patients with optic neuritis; however, the test appears to have clinical usefulness as a method to measure high-contrast and low-contrast acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Vision: Visual acuity under conditions of reduced contrast and reduced luminance were assessed using the Smith-Kettlewell Institute Low Luminance (SKILL) Card. 39,40 The SKILL Card consists of a low-contrast (14%) reading chart comprised of black letters on a dark gray background (10% of the reflectance of white paper) and a high-contrast black-onwhite letter chart (90% of the reflectance of white paper). Participants read the letters aloud line-by-line from a viewing distance of 16 inches (40 cm) using habitual vision (i.e., while wearing their glasses/contact lenses).…”
Section: Methodsmentioning
confidence: 99%
“…Vision: Visual acuity under conditions of reduced contrast and reduced luminance were assessed using the Smith-Kettlewell Institute Low Luminance (SKILL) Card. 39,40 The SKILL Card consists of a low-contrast (14%) reading chart comprised of black letters on a dark gray background (10% of the reflectance of white paper) and a high-contrast black-onwhite letter chart (90% of the reflectance of white paper). Participants read the letters aloud line-by-line from a viewing distance of 16 inches (40 cm) using habitual vision (i.e., while wearing their glasses/contact lenses).…”
Section: Methodsmentioning
confidence: 99%
“…Contrast sensitivity losses in optic neuritis are well known and often take longer to recover than high-contrast acuity losses. 5 Testing for contrast losses is not difficult. The Pelli-Robson wall chart has been used in many studies, including that reported in this issue.…”
mentioning
confidence: 99%